Back view of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The rear side of the temple faces the road. The rear portion of the garbhagriha has a jangha and shikhara. It is noticeable that the shikhara is plain and simple, unlike the jangha, indicating that the shikhara is likely a later renovated structure. The temple is surrounded by a boundary wall comprising broken parts and fragments of the temple. The present temple complex has various trees and plants inside it, evoking ancient descriptions that temples were often nestled in groves as it was believed that gods liked to reside in nature (groves).